(Invited) Probing Semiconductor Heterostructures from the Atomic to the Micrometer Scale. (8th September 2020) - Koelling, Sebastian; Assali, Simone; Atalla, Mahmoud; Kumar, Aashish; Attiaoui, Anis; Lodari, Mario; Sammak, Amir; Scappucci, Giordano; Moutanabbir, Oussama
Abstract : Atom Probe Tomography (APT) has significantly advanced our ability to characterize buried interfaces and to map the three-dimensional distribution of atomic constituents like dopants in modern day electronic nano-devices. This precise mapping of the chemical composition and buried interfaces is also highly sought-after in the implementation and optimization of a variety of emerging photonic devices with dimensions of up to several micrometers as opposed to the few ten nanometers of modern day transistors. Herein, we show that APT is poised to contribute to the development of these devices by adapting the Focused Ion beam based preparation of APT specimen, typically used for preparing semiconductor samples. Using in-situ grown nanowires as sacrificial masks during specimen preparation, we demonstrate APT analyses of micrometer-sized volumes of semiconductor heterostructures.